The effect of gender on SIP investment behavior: An Analysis of risk tolerance and confidence among Bangladeshi male and female investors from capital market industry - Munira, Ishrat Sultana (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.